PO42 | Acquired Von Willebrad syndrome in patients with myeloproliferative syndrome: literature review and single-center experience (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Acquired von Willebrand Syndrome (AvWS) is a rare bleeding disorder, exhibiting clinical and laboratory features similar to hereditary von Willebrand Disease (vWD). Unlike vWD, which stems from genetic defects in von Willebrand factor (vWF), AvWS occurs primarily in adults without a history of bleeding diatheses. AvWS is related with cardiovascular diseases, solid and hematologic malignancies and autoimmune diseases. This study aims to review the latest data on the pathophysiology, clinical presentation, laboratory findings, and treatment of AvWS, focusing on its occurrence in myeloproliferative syndromes. We will also discuss cases from the Hemostasis and Thrombosis Center of AOU Renato Dulbecco in Catanzaro.